VETERINARY PROBLEMS OF REINDEER HUSBANDRY IN THE EUROPEAN NORTH OF RUSSIA - E. S. Kazanovsky; V. P. Karabanov; K. A. Klebenson (Российский паразитологический журнал, 2016)
Objective of research. As deer are kept year-round on pasture (in summer in tundra in the northern coast of the Russian arctic; in winter – in forest-tundra and northern taiga), biogeocenosis and natural focality of most parasitic and infectious diseases were formed over the years. That should be considered when developing methods for combating them, and to determine the optimal timing of mass treatment and prevention measures.Materials and methods. The question naturally arises, which living and nonliving components ensure pathogen survivability, contribute to the emergence and spread of infectious and invasive diseases. Each disease is characterized by specific factors requiring careful examination and generalization based on the study of clinical records and epizootic diseases in reindeer of the European North of Russia.Results and discussion. Dominant diseases of reindeer in the European region ofNorthern Russia, requiring greater attention of veterinary experts and against which it is necessary to conduct a regular complex of veterinary, prevention and treatment measures are: anthrax, edemagenosis, cephenomiosis, necrobacillosis, echinococcosis, cysticercosis, rabies, leptospirosis, number of helminthoses (strongylatosis, monieziasis, echinococcosis, cysticercosis, etc.). This is a brucellosis-free region, and for many tens years no outbreaks of FMD were reported.  The vast majority of the tundra is located in the permafrost zone; the area is dotted with numerous canals, lakes, rivers, streams, marshes, between which in summer on shallow layered soil, grow bushes of willow, dwarf birch, berries, grass and lichen, the main food of deer. The fauna of the tundra is rich and diverse. Here live wolves, foxes, bears, rodents (lemmings, mice), rabbits, birds (geese, ducks, partridges, gulls) and other animals. In summer, "clouds" of midges (mosquitoes, midges, horseflies, flies) are flying in the air. In the region, there are still places virtually untouched by man.  However, in recent years, intensive industrial development of the region began to carry out exploration and extraction of oil, gas and other minerals. Oil and gas pipelines, roads, power lines are built which certainly cannot affect negatively the extremely vulnerable nature of the North. For example, reindeer moss trampled or torn down by moving offroaders can be restored only after 7-10 years. Summer season in the North is a very short period, there are usually few warm and sunny days. These negative factors lead to reduced pastures and do not contribute to the growth of the deer population, their health status and fatness.